Metal concentration in indoor dust of university hostel / Fazrul Razman Sulaiman and Nurul Shuhadah Baharuddin - Sulaiman, Fazrul Razman; Baharuddin, Nurul Shuhadah (Universiti Teknologi MARA Cawangan Pahang, 2020)
Indoor dust has received much attention and can act as a medium for contaminant deposition, including heavy metal. This study determines the concentration of selected metal in indoor dust collected from a hostel building at Universiti Teknologi MARA Cawangan Pahang, Malaysia. This study estimates the potential health risk of indoor dust exposure. Iron (Fe), copper (Cu), lead (Pb) and cadmium (Cd) were analysed using Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES). Fe dominated the results with a range of 1.28-2.50 μg/g, followed by Cu (0.37-0.76 μg/g), Pb (0.02-0.09 μg/g), and Cd (0.01-0.05 μg/g). Enrichment factor (EF), with values less than 10, suggests a mix of anthropogenic and natural sources of metal origin. The total hazard quotients (HQ) were below the level of 1, indicating low non-carcinogenic risks to adults. A comprehensive indoor dust monitoring and health risk assessment could be proposed to minimise the exposure risk in the indoor environment.